2020
DOI: 10.21203/rs.3.rs-27868/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Media Exposure to COVID-19 Information, Risk Perception, Social and Geographical Proximity, and Self-Rated Anxiety in China

Abstract: Background The coronavirus disease 2019 (COVID-19) is an emerging infectious disease that spreads around the world. The lack of effective antiviral drugs and vaccines, along with the relatively high mortality rate and high contagiousness, has raised strong public concerns over COVID-19, especially for people living in the most severely affected areas. This study aimed to clarify the influencing factors for the anxiety level among the Chinese people during the COVID-19 pandemic, with a particular focus on the m… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
2
0
0
Order By: Relevance
“…This finding is consistent with existing Chinese literature analyzing childbirth willingness from online texts [25,26]. Previous studies showed that there are often more negative posts on fertility-related topics on Weibo [14], TikTok [27], WeChat [28], and other social media platforms in China. By analyzing the trend of women's attitudes toward childbirth, we found that the proportion of posts expressing a negative attitude fluctuates and rises over time.…”
Section: Principal Findingssupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with existing Chinese literature analyzing childbirth willingness from online texts [25,26]. Previous studies showed that there are often more negative posts on fertility-related topics on Weibo [14], TikTok [27], WeChat [28], and other social media platforms in China. By analyzing the trend of women's attitudes toward childbirth, we found that the proportion of posts expressing a negative attitude fluctuates and rises over time.…”
Section: Principal Findingssupporting
confidence: 91%
“…This negativity can affect social media users through emotional contagion [34]. In line with previous findings on the relationship between social media and risk perceptions [28], this paper concludes that social media indeed increase women's childbirth risk perceptions. Taking a step further, this paper also provides specific examples for the expansion of women's risk perception.…”
Section: Concept Of Childbirthsupporting
confidence: 88%